Robotic-Assisted Radical Prostatectomy after the First Decade: Surgical Evolution or New Paradigm. (3rd April 2013) - Skarecky, Douglas W.
Abstract : Early studies indicate that robotic-assisted radical prostatectomy (RARP) has promising short-term outcomes; however, RARP is beyond its infancy, and the long-term report cards are now beginning. The important paradigm shift introduced by RARP is the reevaluation of the entire open radical prostatectomy experience in surgical technique by minimizing blood loss and complications, maximizing cancer free outcomes, and a renewed assault in preserving quality of life outcomes by many novel mechanisms. RARP provides a new technical "canvas" for surgical masters to create upon, and in ten years, has reinvigorated a 100-year-old "gold standard" surgery.